A modified surgical model of hind limb ischemia in ApoE-/- mice using a miniature incision - Yan, Kaixuan; Zheng, Jiaxing; Zöllner, Frank G.; Schwenke, Kay; Pallavi, Prama; Keese, Michael (JoVE. Video journal, 2021)
The purpose of this study is to introduce and evaluate a modified surgical approach to induce acute ischemia in mice that can be implemented in most animal laboratories. Contrary to the conventional approach for double ligation of the femoral artery (DLFA), a smaller incision on the right inguinal region was made to expose the proximal femoral artery (FA) to perform DLFA. Then, using a 7-0 suture, the incision was dragged to the knee region to expose the distal FA. Magnetic resonance imaging (MRI) on bilateral hind limbs was used to detect FA occlusion after the surgery. At 0, 1, 3, 5, and 7 days after the surgery, functional recovery of the hind limbs was visually assessed and graded using the Tarlov scale. Histologic evaluation was performed after euthanizing the animals 7 days after DLFA. The procedures were successfully performed on the right leg in ten ApoE-/- mice, and no mice died during subsequent observation. The incision sizes in all 10 mice were less than 5 mm (4.2 ± 0.63 mm). MRI results showed that FA blood flow in the ischemic side was clearly blocked. The Tarlov scale results demonstrated that hind limb function significantly decreased after the procedure and slowly recovered over the following 7 days. Histologic evaluation showed a significant inflammatory response on the ischemic side and reduced microvascular density in the ischemic hind limb. In conclusion, this study introduces a modified technique using a miniature incision to perform hind limb ischemia (HLI) using DLFA.